Quaternary and Pliocene sea-level changes at Camarones, central Patagonia, Argentina - Karla Rubio-S; oval; Deirdre D. Ryan; Sebastian Richiano; Luciana M. Giachetti; Andrew Hollyday; Jordon Bright; Evan J. Gowan; Marta Pappalardo; Jacqueline Austermann; Darrell S. Kaufman; Alessio Rovere (Quaternary Science Reviews, 2024)
Geological indicators of past relative sea level changes are fundamental to reconstruct the extent of former ice sheet during past interglacials, which are considered analogs for future climate conditions. Four interglacials, dating from Holocene to Pliocene, have left sea-level imprints in the proximity of the coastal town of Camarones in Central Patagonia, Argentina. Sea-level index points were preserved as beach ridges deposited by storm waves above modern sea level. We used highly accurate survey techniques to measure the elevation of these deposits. Satellite derived wave measurements and wave runup models were then employed to calculate their indicative meaning (i.e., their elevation with respect to sea level at the time of deposition). The paleo relative sea levels (i.e., uncorrected for post-depositional vertical land motions) associated with the four interglacials (with ±1σ uncertainties) are 6 ± 1.5 m (late Holocene); 8.7 ± 2.1 m (MIS 5e); 14.5 ± 1.5 m (MIS 9 or 11); and 36.2 ± 2.7 m (Early Pliocene). Ages have been obtained using both published (U-series, Electron Spin Resonance, and Radiocarbon) and new (Amino Acid Racemization and Radiocarbon) dating constraints. We compare our results with published glacial isostatic adjustment and mantle dynamic topography predictions, and we highlight that refining these models before calculating the global mean sea level for the interglacials mentioned above is necessary. Our high-resolution sea-level index points serve as an important contribution to the record of paleo relative sea-level in the Southwestern Atlantic.